Effect of sarcopenia on the outcomes after pancreaticoduodenectomy for distal cholangiocarcinoma. Issue 9 (1st February 2018) - Umetsu, Satoko; Wakiya, Taiichi; Ishido, Keinosuke; Kudo, Daisuke; Kimura, Norihisa; Miura, Takuya; Toyoki, Yoshikazu; Hakamada, Kenichi
Abstract : Background: The relationship between sarcopenia and patient outcomes after pancreaticoduodenectomy (PD) for distal cholangiocarcinoma (DCC) remains unclear. We assessed the impact of sarcopenia on the outcomes after PD for DCC. Methods: We retrospectively analysed 65 patients who underwent PD for DCC. The quality of skeletal muscle indicated by the psoas muscle mass index (PMI) were measured on pre‐operative computed tomography images. The impact of pre‐operative sarcopenia on short‐ and long‐term outcomes was evaluated. Results: Regarding short‐term surgical outcomes, there were no marked differences between the high and low PMI groups. Regarding long‐term oncological outcomes, the rates of recurrence (23.5% versus 58.3%, P = 0.011) was significantly lower in the high PMI group than in the low PMI group. Furthermore, the recurrence‐free survival and disease‐specific survival were longer in the high PMI group ( P = 0.023 and P = 0.043, respectively). On multivariate analyses, low PMI was an independent predictor of recurrence (hazard ratio (HR) 11.06; P = 0.022) and disease‐specific death (HR 11.88; P = 0.043). Conclusions: Our findings suggested an association between pre‐operative sarcopenia and poor long‐term oncological outcomes after PD for DCC.